Produtividade da cana-de-açúcar e definição de zonas específicas de manejo do solo - Dalchiavon, Flavio Carlos; Passos e Carvalho, Morel de [UNESP]; Andrade, Flavio Gomes de [UNESP]; Montanari, Rafael [UNESP]; Andreotti, Marcelo [UNESP] (Universidade Estadual de Londrina (UEL), 2013)
The correct spatial intervention in the administration of the plantation, arising from specific areas of soil mapping, can increase your productivity as well as profitability and yields in agriculture. The spatial and Pearson's relationships between sugarcane attributes and chemical attributes of a Typic Tropustalf were studied in the growing season of 2010, in Suzanapolis, State of Sao Paulo, Brazil (20 degrees 27'33 '' S lat.; 51 degrees 08'05 '' W long.), in order to obtain the attributes that had the best sugarcane productivity relationship. To this end, a geostatistical grid containing 118 sample points was installed for soil and plant data collection in an area of 10.5 ha with the third crop cut. The productivity of sugarcane (PRO) represented the attribute of the plant, while the attributes of the soil were: K+, Ca+2, Mg+2 and organic matter at depths of 0-0.20 m and 0.20-0.40 m. Relationships were calculated between the PRO and the attributes of the soil. Semivariograms were adjusted for all attributes, obtaining the respective krigings and the cross-validations. It was also made the cokrigings between the PRO and the soil attributes. The levels of the soil organic matter, for their evident substantial correlations, Sperman's Rho and spatial, with the productivity of sugarcane, are indicators of two specific areas of soil management strongly associated with the productivity of sugarcane. In such zones this productivity varies between 75.8-94.7 t ha(-1) and 101.0-119.9 t ha(-1), when the levels of organic matter respectively are 12.7-14.5 g dm(-3) (0-0.20 m) and 11.8-12.8 g dm(-3) (0.20-0.40 m).
Productivity of the sugarcane and definition of specific zones of soil management
Keywords: Geostatistical; soil management and conservation; Saccharum spp.; spatial variability